THE MEANING OF THE VERB â€œTO SOUNDâ€ IN MUNA LANGUAGE: NATURAL SEMANTIC METALANGUAGE - La Aso (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract This paper aims at investigating the variations of lexicon having meaning of â€œproduce of soundâ€ in Muna language based on natural semantics metalanguage. The data collecting was done by participant speaking and scrutinize methods through interview and noting techniques. It was analyzed by using natural semantics metalanguage (NSM), an approach to investigate various lexicons with principle â€œone form for one meaning and one meaning for one formâ€. Based on the result of this study founded that meaning of â€œproduce of soundâ€ of Muna can be expressed by a number of lexicons and each form has distinctive meaning like in the lexicons of kobheghu, kobhondu, kotighi, kopisi, korasa, korangku, kondii, konduu, kopere, kombote, kopaka, koradha, kobuu, korapa, and kohuhu. All lexicons of Muna language has meaning â€˜produce of soundâ€™. The use of each lexicon depends on the sounded object/tool, object/tool that create the sound, and the way of creating the sound. Keywords: produce of sound, natural semantics metalanguage, distinctive